2012
DOI: 10.1055/s-0032-1309024
|View full text |Cite
|
Sign up to set email alerts
|

Die Wirksamkeit von Ultraschallanwendungen im Vergleich zu Leistungslaser hinsichtlich der Schmerzintensität bei Patienten mit Störungen der LWS und der Schulter

Abstract: Zusammenfassung ▼ Hintergrund: In Deutschland leiden ca. 5-8 Millionen Menschen an chronischen Schmerzen. Dies kostet den Staat ca. 20 Milliarden €/Jahr. Eine wenig untersuchte nichtmedikamentöse Schmerztherapie stellt die Anwendung von Leistungslasern dar. Material und Methoden: In der vorliegenden Studie wurde die Wirksamkeit von Ultraschallanwendungen im Vergleich zu Leistungslaser hinsichtlich der Schmerzintensität untersucht. Es wurden 20 Patienten des Instituts für Physiotherapie des Universitätsklinikum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…23 Best and colleagues' study on patients with lumbar spine or shoulder disorder showed that both US and HILT reduced the intensity of regional pain, but HILT was more effective, which was consistent with the results of the present study. 24 Fiore et al also compared the effect of US and HILT on LBP and found a greater pain reduction in the HILT group. 25 In the present study, most aspects of neck pain were higher in the HILT group at the beginning of the study and before the intervention, and it seems that neck pain was more severe in the participants of this group before the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Best and colleagues' study on patients with lumbar spine or shoulder disorder showed that both US and HILT reduced the intensity of regional pain, but HILT was more effective, which was consistent with the results of the present study. 24 Fiore et al also compared the effect of US and HILT on LBP and found a greater pain reduction in the HILT group. 25 In the present study, most aspects of neck pain were higher in the HILT group at the beginning of the study and before the intervention, and it seems that neck pain was more severe in the participants of this group before the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…21 Several studies have shown the anti-nociceptive effect of HILT. [22][23][24][25][26] In the study of Kim et al 22 and Nazari et al, 23 HILT was more effective than US treatment in controlling pain in patients with knee osteoarthritis. Other studies have shown a superior effect for HILT than US in controlling pain due to lumbar spine and shoulder disorders, 24 LBP, 25 and sub-acromial impingement syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Seit einigen Jahren werden in verschiedenen Disziplinen der Medizin Laserbehandlungen durchgeführt [4]. Wie Best et al zeigen konnten, war die Applikation eines Hochleistungslasers als Monothermotherapeutikum gegenüber herkömmlicher Ultraschalltherapie überlegen bei der Behandlung myofaszialer Schmerzen [5]. Im Behandlungsalltag werden oft Heilmittelkombinationen rezeptiert.…”
Section: Introductionunclassified
“…Das ist eine Besonderheit dieses Assessments.Bezogen auf den SF-36 zeigt die Auswertung der Ergebnisse nahezu unveränderte Mittelwerte der mentalen Summenparameter (MCS) zu den Messzeitpunkten T0 bis T3. Die physischen Parameter, zusammengefasst im Summenscore PCS verbessern sich im gleichen Messzeitraum um einen geringen Wert(5,4). Zu berücksichtigen ist, dass die altersnormierten Durchschnittswerte für den PCS und den MCS bei 50 liegen und die einfache Standardabweichung somit einen Normbereich zwischen 40 bis 60 Punkten definiert.…”
unclassified
“…Since some years laser therapies are performed in different disciplines of medicine [4]. Best et al were able to prove that a high intensity laser application as a mono thermotherapeutic outmatches con ventional ultrasound therapy with regards to the treatment of myofascial pain [5]. If a defined laser therapy is able to affect functional health in a positive manner in comparison to ultra sound applications is therefore the issue of interest.…”
mentioning
confidence: 99%